Naked Mole‐Rat, a Rodent with an Apolipoprotein A‐I Dimer. Issue 3 (17th December 2020) - Puppione, Don L.; Tran, Denise P.; Zenaidee, Muhammad A.; Charugundla, Sarada; Whitelegge, Julian P.; Buffenstein, Rochelle
Abstract: A variety of rodents have been used as experimental animals in metabolic studies of plasma lipids and lipoproteins. These studies have included understanding the functional role of apolipoprotein A‐I, the major protein on the surface of HDL. Reviewing the genomic database for entries for rodent apoA‐I genes, it was discovered that the naked mole‐rat ( Heterocephalus glaber ) gene encoded a protein with a cysteine at residue 28. Previously, two cases have been reported in which human heterozygotes had apoA‐I with cysteine at residues 173 (apoA‐I Milano) or at 151 (apoA‐I Paris). Interestingly, both groups, in spite of having low levels of HDL and moderately elevated plasma triacylglycerols, had no evidence of cardiovascular disease. Moreover, the presence of the cysteine enabled the apoA‐I to form both homodimers and heterodimers. Prior to this report, no other mammalian apoA‐I has been found with a cysteine in its sequence. In addition, the encoded naked mole‐rat protein had different amino acids at sites that were conserved in all other mammals. These differences resulted in naked mole‐rat apoA‐I having an unexpected neutral pI value, whereas other mammalian apoA‐I have negative pI values. To verify these sequence differences and to determine if the N‐terminal location of C28 precluded dimer formation, we conducted mass spectrometry analyses of apoA‐I and other proteins associated with HDL. Consistent with the genomic data, our analyses confirmed the presence of C28 and the formation of a homodimer. Analysis of plasma lipids surprisingly revealed a profile similar to the human heterozygotes.